(untitled) (Journal of Health, Technology and Science (JHTS), 2020)
Jicama seeds contain rotenone which is a poisonous isoflavonoid as a broad-spectrum insecticide and has an influence on insect mortality. This study aims to know the effectiveness of Jicama Seed Extract and the effective concentration of Jicama Seed extract as a vegetable insecticide to-wards the mortality of rice lice. The jicama seed extract was divided into 5 treatments with one control namely 1.00%, 5.00%, 10.00% and 15,00% with each one three repetitions. The results of the study were analyzed using parametric prerequisite tests. The normality test is used Kolmogorov-Smirnov, and Homogeneity test used Levene’s test. For hypothesis 1 analyzed using the F-test (One Way ANOVA) then hypothesis 2 is analyzed using the Duncan test. The results of the study showed there is an influence of Jicama seed extract (Pachyrizus erosus (L.) Urban) as a vegetable insecticide towards the mortality of rice lice (Sitophilus oryzae) which is indicated by the value of sig. amounting to 0.00 <0.05 and an effective concentration of Jicama seed extract as a vegetable insecticide towards the mortality of rice lice is at a concentration of 15.00%